Voice from the frontline and learning for the future: A qualitative descriptive study on wider perspectives of frontline nurses in India during the COVID 19 global pandemic - Sunita Panda; Manjubala Dash; Rajalaxmi Mishra; Shilpa A. Shettigar; Delphina Mahesh Gurav; Sathiya Kuppan; Santhoshkumari Mohan (Elsevier, 2023)
Objective: This study was conducted to explore frontline nurses' experiences of the impact of COVID 19 pandemic and suggestions for improvement in the healthcare system, policy and practice in the future. Method: A qualitative descriptive design was used. Frontline nurses who were involved in providing care to patients affected with COVID 19 in four designated COVID units from the Eastern, Southern and Western regions of India were interviewed during January to July 2021. Interviews were audio-recorded and transcribed manually by researchers from each region and thematically analysed. Result: Twenty-six frontline nurses aged between 22 and 37 years with a range of 1-14 years of work experience following a Diploma or Bachelor's degree in Nursing and Midwifery and working in the COVID units of selected regions in India participated in the study. Three key themes emerged: 'Physical, emotional and social health - an inevitable impact of the pandemic' described effects of the pandemic on nurses' health and wellbeing; 'Adapting to the uncertainties' narrated how nurses accommodated to the uncertainties during the pandemic; and 'An agenda for the future - suggestions for improvement' emphasised on practical strategies for the future. Conclusion: The inevitability of the pandemic had an influence at a personal, professional, and social level with learning for the future. The findings of this study have implications for healthcare system and facilities by enhancing resources, supportive environment for staffs to cope with the challenges imposed by the crisis and ongoing training to manage life threatening emergencies in the future.